Festivals and the Theory of Inclusive Development in Malaysia: Perspectives from a Festival Organizer - Goh, Yi Sheng *; Teh, Pek Yen * (Society of South-East Asian Studies (SEAS), 2022)
Festivals play a vital role in catalyzing inclusive development through their ability to increase social capital. They can enhance social ties through creating shared knowledge, building trust, and forming networks. In the Malaysian context, few studies have been done on how festivals promote inclusive development. Hence, this paper seeks to present a case study on Pangkor Island Festival (PIF), which is a Malaysian arts and culture festival, concerning the process, opportunities, and challenges of inclusive development from the perspectives of the festival organizer. In-depth interviews with the festival organizer and curator and field observations were conducted. Findings show that festivals promote inclusive development through a five-phase process, from establishing relationships with residents and exploring local assets to the sustainability of PIF and inclusive development. This study also suggests three-fold opportunities that include community cohesiveness, revitalization, and cultural value restoration as well as challenges of securing suitable stakeholders.